On the South Equatorial Undercurrent Origin and Variability in the Western Tropical Atlantic - Araujo, Julia Martins de (2022)
The South Equatorial Undercurrent (SEUC) is the northermost equatorial countercurrent of the South Atlantic Ocean. Having been described in the late 1970s, this jet has been depicted as lower tropical pycnocline-subpycnoclinic current that flows eastward crossing the Atlantic Ocean in the 3.5°S-5.5°S latitudinal band. Its origin site is nearby the western boundary, but how this jet is formed and organizes itself is theme that has not been settled in the scientific community so far. Some authors credit the SEUC genesis due to the feeding by the western boundary current system. Others consider that the SEUC is formed by interior sources, such as the equatorial branch of the South Equatorial Current (eSEC) as it approaches the Brazilian continental margin. Finally, there are others who compromise both approaches mentioning that the SEUC genesis is seasonally-dependent and its sources may vary along the year. However, most of this studies used one-two cruise synoptic observations and/or limited float data. This present work aims to reexamine this topic by obtaining a higher resolution, quantitative picture of the SEUC origin site employing hydrographic and current profiler data from 25 surveys in the area. It complements the observational information by exploring the 1993-2018 assimilative GLORYS12V1 global reanalysis. The analysis and interpretation of 13 selected cruises that best captured the SEUC suggested - through the construction vertical section and stream function maps - that the North Brazil Undercurrent (NBUC) is the main source of water volume to the SEUC. The SEUC orgin seems to be closely related to a southernmost of the multiple retroflections of the NBUC-North Brazil Current (NBC) system. However, unlike all others, the retroflection lobe is cyclonic, and not anticyclonic. In addition, the sometimes called NBUC counterflow (or NBUCc for short) is in fact and overshoot of the so-called primary crest of the retroflection structure, and very likely the SEUC begining. The site location of the NBUC retroflection is that of the shelf projection of the Cape Calcanhar (5.5°S), where the Brazilian margin veers drastically from a meridional orientation to virtually 45° westward of the north direction. In addition to the veloctiy mapping, a regional water mass analysis was carried out to reveal that lower salinity, high dissolved oxygen content, and therefore compatible with the SACW flowing in the NBUC, dominates the SEUC near its origin location. The uneven distribution of the 13 analyzed cruises led us to rule out the possiblity of seasonaly alternating sources of SEUC feeding. The NBUC source is markly relevant throughout the year. The use of the numerical GLORYS12V1 outputs allowed for three complementing and relevant results, after a detailed quantitative assessment of the model skills in the study area. The first result was to compute a 25-year climatology of the SEUC birth site, calculate the volume transport balance and show that the NBUC feeding cannot be discarded as the most important source for the SEUC formation. A second relevant finding is that the the use of AMEDA eddy-detecting algorithm allowed to separate three large bands rich in vortical activity. The northeast band (2.5°S-4.5°S,35°W-28°W) is dominated by anticyclones; the southeast band (4.5°S-6.5°S,35°W-28°W) is dominated by cyclones and the western boundary(0°-3.5°S,39°W -35°W) band is also dominated by cyclones. The first two zonal bands are separated by a slimmer region were both polarities are found. All this is indicative of the presence of a wave pattern characteristic of separating jets from a retroflection structure. Moreover, the inspection of countless model snapshots revealed that these waves are unstable - probably baroclinic Tropical Instability Waves- already reported for the region and related somehow withthe SEUC dynamics. The third and, perhaps the most intriguing, of the three results of the numerical output analysis is that the NBUC retroflection itself is unstable, and sheds about 7 intrapycnoclinic cyclones per year. These rings keep flowing northwestward bordering the NBC and probably reach the equator.